Multiagent voltage and reactive power control system - Arkhipov, I.; Molskij, A.; Ivanov, A.; Novickij, D.; Sorokin, D.; Holkin, D. (EAI Endorsed Transactions on Energy Web, 2014)
This paper is devoted to the research of multiagent voltage and reactive power control system development. The prototype of the system has been developed by R&D Center at FGC UES (Russia). The control system architecture is based on the innovative multiagent system theory application that leads to the achievement of several significant advantages (in comparison to traditional control systems implementation) such as control system efficiency enhancement, control system survivability and cyber security.